2011
DOI: 10.1016/j.hrthm.2010.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Classifying fractionated electrograms in human atrial fibrillation using monophasic action potentials and activation mapping: Evidence for localized drivers, rate acceleration, and nonlocal signal etiologies

Abstract: BACKGROUND Complex fractionated electrograms (CFAEs) detected during substrate mapping for atrial fibrillation (AF) reflect etiologies that are difficult to separate. Without knowledge of local refractoriness and activation sequence, CFAEs may represent rapid localized activity, disorganized wave collisions, or far-field electrograms. OBJECTIVE The purpose of this study was to separate CFAE types in human AF, using monophasic action potentials (MAPs) to map local refractoriness in AF and multipolar catheters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
2
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(134 citation statements)
references
References 30 publications
(40 reference statements)
1
129
2
2
Order By: Relevance
“…CFAE signals may be caused by electrogram filtering methods or farfield potentials. 25 Relative to AF dynamics, they depend on rate and activation wavefront and may be because of passive phenomena as wave collisions, pivot points, or slow/anisotropic conduction, but also may be linked to AF perpetuation in meandering rotors. [25][26][27][28][29][30] In previous studies, ablation of continuous CFAE sites was associated with the highest impact on AF, producing AF slowing or termination at 50% of ablated continuous CFAE sites.…”
Section: Discussionmentioning
confidence: 99%
“…CFAE signals may be caused by electrogram filtering methods or farfield potentials. 25 Relative to AF dynamics, they depend on rate and activation wavefront and may be because of passive phenomena as wave collisions, pivot points, or slow/anisotropic conduction, but also may be linked to AF perpetuation in meandering rotors. [25][26][27][28][29][30] In previous studies, ablation of continuous CFAE sites was associated with the highest impact on AF, producing AF slowing or termination at 50% of ablated continuous CFAE sites.…”
Section: Discussionmentioning
confidence: 99%
“…These include pharmacological interventions, the use of monophasic action potentials, limiting ablation to areas of continuous electrical activity, and activation mapping of AF. 540,548,549,550,551 Unfortunately, improved outcomes with CFAE ablation in patients with persistent AF have not been uniformly reported, and the scientific basis for CFAE ablation is not universally accepted. Moreover, results from the STAR AF II trial have shown that the addition of further ablation (lines or CFAEs) to PVI increased ablation time but did not reduce the recurrence of AF in 589 patients with persistent AF.…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
“…55 Given the predominantly functional nature of CFAEs, however, this explanation seems unlikely, and Narayan's group has demonstrated that CFAEs are largely spatially unrelated to sites of rotors or other focal AF drivers. 70 Nevertheless, all CFAEs may not be equivalent, 71 and fractionation may evolve over time as AF transitions from paroxysmal to persistent. 72 Ablation of fractionated electrograms which demonstrate continuous activity or temporal activation gradients have been shown to be more strongly associated with AF slowing or termination, 73 and the subset of CFAEs that persist in AF, sinus rhythm or with atrial pacing might also be important in the pathophysiology of AF, with a potential role as an ablation target.…”
Section: Complex Fractionated Electrograms Are Passive Bystanders In Afmentioning
confidence: 99%